(untitled) (Research, Society and Development, 2021)
Deep vein thrombosis (DVT) is defined as a thrombotic event involving the deep veins of the lower limbs, popliteal, femoral or iliac veins. DVT is usually accompanied by pulmonary embolism (PE) and venous thromboembolism (VTE) is a term used to specify both possibilities. Thus, this research aimed to carry out a literature review on the use of anticoagulants in hospitalized patients and the role of the pharmacist in guiding the multidisciplinary hospital team on the proper use of drugs. This is a literature review using a qualitative approach, using secondary sources to describe the use of anticoagulants in patients with deep vein thrombosis in the lower limbs. Through the results obtained, it appears that it is up to the pharmacist to instruct the patient about the use of the drug, dose, best time of administration, drug interaction, in addition to healthy habits in non-therapeutic care, being able to make interventions that range from simple signaling from an interaction, to suggestions for alternative therapies or adjustments to the doses prescribed by the physician, when any error or problems related to the therapy are identified. This adjustment must be documented and informed to the prescribing physician, constituting a link between pharmacist, physician and patient.